2020
DOI: 10.1016/j.jcot.2019.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondromas of the cervical spine-case series and review

Abstract: Objective: Cervical spine osteochondromas are rare with approximately 3% of solitary and 7e9% of hereditary osteochondromas occurring in the spine. Almost 50% of spinal osteochondromas occur in the cervical region. Methods: A search of osteochondroma of cervical spine was performed of our radiology database. Results: In this study, we present 11 cases of adult cervical spine osteochondromas. These predominantly involved the posterior elements. The cartilage cap was more than 2 cm in 2 cases. There was cord com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Osteochondromas may occur in the spine, these are rare lesions and constitute less than 4% of spinal neoplasms, and about 50% of spinal osteochondromas occur in the cervical region [4,[7][8][9][10]. The index case belongs to the rare 4% of spinal neoplasm and 50% of those within the cervical region, thereby conforming to these literatures.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Osteochondromas may occur in the spine, these are rare lesions and constitute less than 4% of spinal neoplasms, and about 50% of spinal osteochondromas occur in the cervical region [4,[7][8][9][10]. The index case belongs to the rare 4% of spinal neoplasm and 50% of those within the cervical region, thereby conforming to these literatures.…”
Section: Discussionsupporting
confidence: 76%
“…When osteochondromas occur in the spine, they are rare lesions and constitute less than 4% of spinal neoplasms [4,[7][8][9]. Almost 50% of spinal osteochondromas occur in the cervical region [10].…”
Section: Introductionmentioning
confidence: 99%
“…On reviewing the literature, a total of 207 articles were published from 2004 to August 2020, of which 92 articles 4 …”
Section: Discussionmentioning
confidence: 99%
“…Spinal osteochondromas are relatively rare, with an incidence rate of 1%–4%. 9 , 12 , 16 Among these, those with neurological symptoms account for .5%–1%. 19 , 20 Of spinal osteochondromas, nearly half of the patients occur in the cervical spine (C2>C3>C6).…”
Section: Discussionmentioning
confidence: 99%
“…It generally arises from osteochondroma near the ends of long bones. Osteochondroma can occur in any part of the bone, but most osteochondromas tend to occur in the knee area [5].Osteochondroma can develop during the growth period of the skeletal system [6].It is generally believed that osteochondroma stops increasing in volume at the end of bone growth [7].However, symptoms in adults are often associated with bone development.Osteochondroma is less likely to occur in the spine and is more likely to occur in men than women (M/F ratio :2.5/1).Data show that only 1.3%-4% of single osteochondromas occur in the spine, and 50% of the cases have lesions in the cervical spine, among which the axial vertebra is most often involved [6],the next most common site is the thoracic vertebra.Some studies have suggested that the microtrauma and displacement of growth cartilage in part of epiphyseal caused by greater stress caused by activity is an important reason for the high incidence of cervical and thoracic osteochondroma.Although the mobility of lumbar vertebrae is much higher than that of thoracic vertebrae, the incidence of lumbar vertebrae is low because the ossification center of lumbar vertebrae generally ossifies around 30 years old, later than that of cervical vertebrae and thoracic vertebrae [8].With age, the cartilage on the surface of osteochondroma will become thin, calcify or ossify, or even disappear [9].Intact cartilage caps are seen in only about 30% of patients.In this case, if the lesion occurred in the lumbar spine,Intraoperative cases with intact cartilage caps are rare.…”
Section: Discussionmentioning
confidence: 99%